The Scarcity Effect of Quantitative Easing on Repo Rates : Evidence from the Euro Area - Arrata, William (IMF Working Papers; Working Paper ;, 2018)
Most short-term interest rates in the Euro area are below the European Central Bank deposit facility rate, the rate at which the central bank remunerates banks' excess reserves. This unexpected development coincided with the start of the Public Sector Purchase Program (PSPP). In this paper, we explore empirically the interactions between the PSPP and repo rates. We document different channels through which asset purchases may affect them. Using proprietary data from PSPP purchases and repo transactions for specific ('special") securities, we assess the scarcity channel of PSPP and its impact on repo rates. We estimate that purchasing 1 percent of a bond outstanding is associated with a decline of its repo rate of 0.78 bps. Using an instrumental variable, we find that the full effect may be up to six times higher.